Toxicity Thresholds for Diclofenac, Acetaminophen and Ibuprofen in the Water Flea Daphnia magna - Du, Juan; Mei, Cheng-Fang; Ying, Guang-Guo; Xu, Mei-Ying (Bulletin of environmental contamination and toxicology, 2016)
Non-steroid anti-inflammatory drugs (NSAIDs) have been frequently detected in aquatic ecosystem and posed a huge risk to non-target organisms. The aim of this study was to evaluate the toxic effects of three typical NSAIDs, diclofenac (DFC), acetaminophen (APAP) and ibuprofen (IBP), toward the water flea Daphnia magna . All three NSAIDs showed remarkable time-dependent and concentration-dependent effects on D. magna , with DFC the highest and APAP the lowest toxic. Survival, growth and reproduction data of D. magna from all bioassays were used to determine the LC10 and LC50 (10 % lethal and median lethal concentrations) values of NSAIDs, as well as the EC10 and EC50 (10 % effect and median effect concentrations) values. Concentrations for the lethal and sublethal toxicity endpoints were mainly in the low ppm-range, of which reproduction was the most sensitive one, indicating that non-target organisms might be adversely affected by relevant ambient low-level concentrations of NSAIDs after long-time exposures.